Compósito de hidrogel e biochar de casca de pinhão: preparo, caracterização e avaliação do potencial uso como fase ligante em dispositivos de difusão em filmes finos por gradiente de concentração (DGT) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
Chromium is a metallic species that has wide use in several industrial sectors. The most stable oxidation states in the environment are Cr(III) and Cr(VI), and these species have completely different chemical characteristics. Cr(III) is considered an essential trace element for humans, while Cr(VI) is toxic and carcinogenic. In the environment, especially in aquatic compartments, the hexavalent form of chromium is the most bioavailable, since trivalent chromium easily forms complexes with humic substances and particulate matter. Thus, it is important to carry out environmental monitoring to control and to differentiate chromium species. One way to accomplish this is through chemical speciation analysis with DGT devices, which are based on the diffusion of elements through a diffusive layer and accumulation in a binding phase. Therefore, in this work, sorbent materials capable of interacting with chromium species were developed and it can be applied in DGT devices as an alternative, low-cost and sustainable binding phase. Agarose hydrogel and biochar of pinhão husk (seed of Araucaria angustifolia) were used as precursor materials. The materials obtained were characterized by techniques such as FTIR, SEM, Zeta potential and surface area BET and BJH. For the sorption assays with Cr species, the biochar of pinhão husk was immobilized in the agarose hydrogel, which was called composite. The experiments were carried out with variation of the proportion of biochar in the composite, different initial concentrations of Cr(III) and (VI), variation of pH and contact time. The best results at pH=7 were obtained using the composite with the lowest proportion of biochar (CP2), in shorter sorption times (3h) for lower Cr concentrations (7 g L-1 ), and the results were 83% and 40% of sorption for Cr(III) and (VI), respectively. In the case of the highest concentration of Cr (40 to 70 g L-1 ) a longer sorption time (24 h) was necessary, in order to obtain the best sorption percentages. The FTIR spectra obtained after sorption with Cr showed that changes occurred, as appearance of bands in the region of 668 to 966 cm-1 , attributed to asymmetric vibrations of Cr-O-Cr. After the construction of the Factorial Design 23 , the best assay conditions were set (CP2, lowest Cr concentration and shortest sorption time) to evaluate the pH variation. The highest sorption percentages were obtained at pH=3, and the results were 86 % for Cr(III) and 61% for Cr(VI). The desorption was carried out with 1 mol L-1 HNO3 to remove the Cr from the material. Two desorption steps were needed to extract the Cr(VI) in the material, while for Cr(III) only one desorption step was sufficient. The results obtained in the chromium sorption and desorption processes indicate that the major interaction mechanism is through the formation of Cr complexes with the functional groups present on the surface of the materials. The material developed can be used in the DGT device as an alternative ligand phase in the chemical speciation of chromium.
Keywords: biocarvão; cromo; hidrogel; especiação química; biochar; hydrogel; chromium; chemical speciation.; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA